2020
DOI: 10.1136/gutjnl-2020-322540
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils interact with cholangiocytes to cause cholestatic changes in alcoholic hepatitis

Abstract: Background & objectivesAlcoholic hepatitis (AH) is a common but life-threatening disease with limited treatment options. It is thought to result from hepatocellular damage, but the presence of cholestasis worsens prognosis, so we examined whether bile ducts participate in the pathogenesis of this disease.DesignCholangiocytes derived from human bile ducts were co-cultured with neutrophils from patients with AH or controls. Loss of type 3 inositol 1,4,5-trisphosphate receptor (ITPR3), an apical intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 50 publications
1
49
0
1
Order By: Relevance
“…Cholangiocytes play a previously unrecognized role in the development of cholestasis in alcoholic hepatitis. 28 We tested ethanol-associated biliary injury in vitro, using hICOs and ALD-ICOs, which potentially are associated with alcoholic liver disease etiology ( Figure 6 A ). The nonoxidative ethanol metabolite palmitoleic acid (POA) has been implicated as a critical mediator in ethanol-evoked epithelial cell injury.…”
Section: Resultsmentioning
confidence: 99%
“…Cholangiocytes play a previously unrecognized role in the development of cholestasis in alcoholic hepatitis. 28 We tested ethanol-associated biliary injury in vitro, using hICOs and ALD-ICOs, which potentially are associated with alcoholic liver disease etiology ( Figure 6 A ). The nonoxidative ethanol metabolite palmitoleic acid (POA) has been implicated as a critical mediator in ethanol-evoked epithelial cell injury.…”
Section: Resultsmentioning
confidence: 99%
“…AH is a potentially lethal complication of alcoholic liver disease, which has been attributed to hepatocellular damage in the past 5 . Recently, binding of neutrophils to ITGB1 expressed on the cell surface of cholangiocytes was shown to contribute to epithelial cell damage and the development of cholestasis in AH 7 . Other studies showed that cholestatic liver injury can be involved in the pathogenesis of AH, moreover, impaired secretion by cholangiocytes, or cholestasis, results in a worse outcome 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that cholestatic liver injury can be involved in the pathogenesis of AH, moreover, impaired secretion by cholangiocytes, or cholestasis, results in a worse outcome 6 . Takeuchi et al highlighted that integrin beta-1 (ITGB1)-mediated binding of neutrophils to cholangiocytes in AH results in the development of cholestasis 7 . It is well-established that cholangiocyte secretion largely depends on the proper function of the apically expressed CFTR 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Cholestasis is the intrahepatic accumulation of toxic bile acids that occurs in several liver diseases, which were caused by various factors, such as pregnancy, drugs, alcohol, etc (Chatterjee and Annaert, 2018;Ovadia et al, 2021;Takeuchi et al, 2021). The occurrence of cholestatic liver diseases is very rare, with an annual incidence of between 0.3/100000 and 5.8/100000 (Wagner and Fickert, 2020).…”
Section: Discussionmentioning
confidence: 99%